2019
DOI: 10.1093/ckj/sfz045
|View full text |Cite
|
Sign up to set email alerts
|

‘WhatsApp®’ening in nephrology training

Abstract: Background Teaching methods in most residency and fellowship programs have not yet addressed the challenges of rapid dissemination of new scientific information. Our Northwell nephrology fellowship program used the smartphone application WhatsApp® to facilitate nephrology education. A qualitative study was conducted to explore perceptions of nephrology fellows and faculty using WhatsApp® as a teaching tool. Methods A WhatsApp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…This study supports both the findings of Giordano et al ,[ 6 ] as well as other reports that prove WhatsApp to be an effective tool for professional health education. [ 7 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…This study supports both the findings of Giordano et al ,[ 6 ] as well as other reports that prove WhatsApp to be an effective tool for professional health education. [ 7 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Comfort and control emerged as the main themes. The finding was that the ease of use, familiarity, and cost-effectiveness of the tool can augment student learning during fellowship (Jhaveri et al, 2020). During the COVID-19 lockdown in India, studies showed that the most common mode of consultation was by WhatsApp messages while email was the least preferred method (Pandey et al, 2020;Kapasia et al, 2020).…”
Section: Collaboration and Learning Supportmentioning
confidence: 99%
“…In higher education contexts in India, most of the published WhatsApp research has been situated in medical education (Bakshi & Bhawalkar, 2017;Jhaveri et al, 2020;Kaliyadan et al, 2016;Kapoor et al, 2016). Bakshi and Bhawalkar (2017) examined second-and third-year anesthesia residents' perception of being in a WhatsApp group with a board-certified anesthesiologist with specialization in pain management, and how WhatsApp discussions in pain management presented through clinical scenarios, resident inquiries, and instructional support benefitted anesthesiology residents.…”
Section: Communicationmentioning
confidence: 99%
“…[2][3][4][5][6][7] In the last decade, online learning tools such as blogs, social media, online journal clubs, videos, games, and texting apps have been embraced by the nephrology community and other specialties. 3,6,[8][9][10] Additionally, social media dissemination of educational content enables quick, broad uptake of these materials.…”
Section: Introductionmentioning
confidence: 99%